All-star - Linda Lee (McGraw-Hill ESL/ELT, 2005)
Aimed at adult English learners, this work features a picture-dictionary approach to vocabulary building. This series has big picture scenes that provide springboards to activities that develop language skills. It provides a step-by-step sequence of lessons to systemically build language and math skills around life-skill topics